2019
DOI: 10.3390/jcm8030346
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of SET is Associated with Tumor Progression and Predicts Adverse Outcome in Patients with Early-Stage Colorectal Cancer

Abstract: SET nuclear proto-oncogene (SET) deregulation is a novel molecular target in metastatic colorectal cancer (CRC). However, its role in CRC progression and its potential clinical impact in early-stage CRC patients remain unknown. Here, we studied the biological effects of SET on migration using wound-healing and transwell assays, and anchorage-independent cell growth using soft agar colony formation assays after ectopic SET modulation. SET was analyzed by immuno-staining in 231 early-stage CRC patients, and miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…We observed that the miR-199b/SET axis plays a key role in determining 5-FU resistance, and both miR-199b and SET predicted the responses to CRT in our LARC cohort [32]. Although SET overexpression has also been described as able to predict worse prognoses in early-stage CRC [33], several differences highlight the prognostic value of miR-199b. This issue is based on the fact that this miR contributes to CRC progression toward the regulation of several other targets besides SET, and that miR-199b was found to be downregulated in around only 50% of cases with metastatic CRC and high SET expression [23].…”
Section: Discussionmentioning
confidence: 71%
“…We observed that the miR-199b/SET axis plays a key role in determining 5-FU resistance, and both miR-199b and SET predicted the responses to CRT in our LARC cohort [32]. Although SET overexpression has also been described as able to predict worse prognoses in early-stage CRC [33], several differences highlight the prognostic value of miR-199b. This issue is based on the fact that this miR contributes to CRC progression toward the regulation of several other targets besides SET, and that miR-199b was found to be downregulated in around only 50% of cases with metastatic CRC and high SET expression [23].…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, our group recently reported that miR-199b downregulation was significantly associated with SET overexpression in a set of 29 CRC patients without metastatic disease. Notably, seven out of 29 cases had SET overexpressed, and three out of those seven SET-overexpressing cases showed a concomitant miR-199b downregulation, which suggests that this alteration is a contributing mechanism to deregulate SET in early-stage CRC [ 39 ]. We observed here an inverse correlation between miR-199 and SET expression in LARC.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the tumor suppressor role of PP2A, the PP2A inhibitors, inhibitor-2 of protein phosphatase-2A (SET) and cancerous inhibitor of PP2A (CIP2A), are overexpressed in a variety of cancers [122][123][124][125][126]. These proteins function to prevent PP2A-B subunits from binding the PP2A A-C core complex, decreasing global PP2A activity and contributing to therapeutic resistance [127,128].…”
Section: Indirect Protein Phosphatase 2a (Pp2a) Activationmentioning
confidence: 97%